Exploring the Three-Dimensional Frontier: Advancements in MSC Spheroids and Their Implications for Breast Cancer and Personalized Regenerative Therapies - Veronika Smolinska; Stefan Harsanyi; Martin Bohac; Lubos Danisovic (Biomedicines, 2023)
To more accurately replicate the in vivo three-dimensional (3D) mesenchymal stem cell (MSC) niche and enhance cellular phenotypes for superior in vivo treatments, MSC functionalization through in vitro 3D culture approaches has gained attention. The organization of MSCs in 3D spheroids results in altered cell shape, cytoskeleton rearrangement, and polarization. Investigations have revealed that the survival and secretory capability of MSCs are positively impacted by moderate hypoxia within the inner zones of MSC spheroids. The spheroid hypoxic microenvironment enhances the production of angiogenic and anti-apoptotic molecules, including HGF, VEGF, and FGF-2. Furthermore, it upregulates the expression of hypoxia-adaptive molecules such as CXCL12 and HIF-1, inhibiting MSC death. The current review focuses on the latest developments in fundamental and translational research concerning three-dimensional MSC systems. This emphasis extends to the primary benefits and potential applications of MSC spheroids, particularly in the context of breast cancer and customized regenerative therapies.